Traditional and corporate food distribution: collective case studies of a semi-rural area San Cristóbal, Medellín-Colombia - Puerta-Zapata, Jenifer; Cadavid-Castro, Martha Alicia; Montoya-Betancur, Karen Valeria; Álvarez-Castaño, Luz Stella (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Food distribution is closely related to territorial socioeconomic transformations. Movements such as urbanization have been linked to the expansion of the corporate distribution model, often to the detriment of traditional forms of commercialization. This article describes food distribution characteristics in a rural area, of which a part has been affected by urbanization. Results were obtained through a qualitative study of collective cases in San Cristóbal, Medellín-Colombia.  Food distribution was found to be influenced by geographic patterns. The corporate model is located within the area with the greatest urban influence, and commercial operations are performed outside the local context of food production. Meanwhile, the traditional model was found widely used throughout the territory, with marked differences in operating conditions, depending on the type of township where this model was operating. These two distribution models co-exist in the territory, and their operational norms contribute to the availability and access to foods, which highlights the importance of these settings in advancing public policies that seek to guarantee food sovereignty and food and nutritional security